Phenylpropanoids isolated from Piper sarmentosum Roxb. induce apoptosis in breast cancer cells through reactive oxygen species and mitochondrial-dependent pathways - Hematpoor, Arshia; Paydar, Mohammadjavad; Liew, Sook Yee; Sivasothy, Yasodha; Mohebali, Nooshin; Looi, Chung Yeng; Wong, Won Fen; Sofian-Azirun, Mohd; Awang, Khalijah (Elsevier, 2018)
The aim of the present study is to isolate bioactive compounds from the roots of Piper sarmentosum and examine the mechanism of action using human breast cancer cell line (MDA-MB-231). Bioassay guided-fractionation of methanolic extract led to the isolation of asaricin (1) and isoasarone (2). Asaricin (1) and isoasarone (2) had significant cytotoxicity towards MDA-MB-231. MCF-10A (human normal breast epithelial cells) cells are less sensitive than MDA-MB-231, but they respond to the treatment with the same unit of measurement. Both compounds increase reactive oxygen species (ROS), decrease mitochondrial membrane potential (MMP) and enhance cytochrome c release in treated MDA-MB-231 cells. Isoasarone (2) markedly elevated caspase -8 and -3/7 activities and caused a decline in nuclear NF-κB translocation, suggesting extrinsic, death receptor-linked apoptosis pathway. Quantitative PCR results of MDA-MB-231 treated with asaricin (1) and isoasarone (2) showed altered expression of Bcl-2: Bax level. The inhibitory potency of these isolates may support the therapeutic uses of these compounds in breast cancer.